The Plurality of Greeknesses in Interwar Greece: A Matter of Culture or Politics? - Papari, Katerina Georgiou (Historein, 2018)
The interwar crisis as perceived by conservative German and Greek intellectuals focused particularly on national identity, which they thought to be decisively challenged and threatened by radical transformation. In Greece the intellectual elites undertook the task to interpret the crisis in order to frame a cultural programme concerning the meaning of Hellenism that incorporated their ideological and partisan assumptions. This article explores the notion of Greekness, and the ways it embraced and encapsulated the problems that bedevilled both state and society, during the period of the interwar crisis. It aims, first, to examine the intellectuals' narrative and production of the ideology of Greekness as a signifier that launched, implicitly and explicitly, the elements that constituted a new imaginary institution of the nation. To this end, it will examine theoretical schemes and cultural transfers from German academic currents and theorists of the time and the appeal of their proclamations. The ideology of Greekness offered a means for the government to resolve the issues of the interwar state and, in particular, the challenge of its political survival and continuity. My second aim is to trace the convergences and divergences of the concervative intellectuals' schema of Greekness with the equivalent aspirations of the Thirties Generation. By capturing the meaning of Greekness, the conservative intelligentsia expanded the criterion for Greekness beyond an aesthetic perception of Hellenism and its related conversation with European modernism, as the issue was employed by the writers and poets of the Thirties Generation. Conservative's examination of Greekness disclosed the way that the politics of culture both served and promoted a hegemonic discourse. In conclusion my paper holds that the intellectuals' main concern was to utilize the cultural capital of Hellenism in order to propose a technique of governance, numbering the Greek case among the counterpart nationalist project in Germany at the time. Greekness demonstrated anew an imaginary conceptualization and institutionalization of the nation, that was articulated in accordance with the ideological assertions of conservatives circles and became synonym with a pedagogy of national conformity.